Windmaker, volume 2 ebook - Akinboye, Sunkanmi (WindMaker, 2023)
The Republic of Atala's president has turned into a ruthless despot, and one of his most trusted associates, Director Bo, is forced to choose a side in a civil war that threatens to destroy their beloved nation.The spirit of the WindMaker—an ancient and powerful protector of the Atalians—also begins to awaken within Bo, a troubled warrior. Is this awakening a ray of hope that will pave a path to salvation, or is this an omen signaling the end of a once prosperous and influential country?YouNeek YouNiverse creator Roye Okupe and his studio of Nigerian comic book creators continue this tale of fate and fury!